Confinement Effect of Plasmon for the Fabrication of Interconnected AuNPs through the Reduction of Diazonium Salts - Luong-Lam Nguyen; Quang-Hai Le; Van-Nhat Pham; Mathieu Bastide; Sarra Gam-Derouich; Van-Quynh Nguyen; Jean-Christophe Lacroix (Nanomaterials, 2021)
This paper describes a rapid bottom-up approach to selectively functionalize gold nanoparticles (AuNPs) on an indium tin oxide (ITO) substrate using the plasmon confinement effect. The plasmonic substrates based on a AuNP-free surfactant were fabricated by electrochemical deposition. Using this bottom-up technique, many sub-30 nm spatial gaps between the deposited AuNPs were randomly generated on the ITO substrate, which is difficult to obtain with a top-down approach (i.e., E-beam lithography) due to its fabrication limits. The 4-Aminodiphenyl (ADP) molecules were grafted directly onto the AuNPs through a plasmon-induced reduction of the 4-Aminodiphenyl diazonium salts (ADPD). The ADP organic layer preferentially grew in the narrow gaps between the many adjacent AuNPs to create interconnected AuNPs. This novel strategy opens up an efficient technique for the localized surface modification at the nanoscale over a macroscopic area, which is anticipated to be an advanced nanofabrication technique.